IoT Based Falling Detection System - Vasuthavan, Kartik; Ismail, Muhammad Nafis (Evolution in Electrical and Electronic Engineering, 2023)
This paper presents a fall detection system for elderly individuals using a smart sensor that can detect changes in body position and notify caregivers when a fall has occurred. The system is designed to be affordable and addresses the issue of falls being a common cause of medical attention required by the elderly, particularly when living alone. The detection algorithm is designed to differentiate between actual falls and normal daily activities (known as Activities of Daily Living or ADLs) in order to reduce false alerts and improve the accuracy of the system. This paper aims to provide a practical solution to combat the issue of falls among the elderly population and to help caregivers provide better care for the elderly.